2013
DOI: 10.1042/bj20121558
|View full text |Cite
|
Sign up to set email alerts
|

ADAM12 is expressed in the tumour vasculature and mediates ectodomain shedding of several membrane-anchored endothelial proteins

Abstract: ADAM (a disintegrin and metalloproteinase) 12 is a metalloprotease implicated in cancer progression. ADAM12 can activate membrane-anchored proteins, such as sonic hedgehog, Delta-like 1 and certain epidermal growth factor receptor ligands, through a process called ectodomain shedding. We screened several membrane-anchored proteins to further dissect the substrate profile of ADAM12-mediated ectodomain shedding, and found shedding of five previously unreported substrates [Kitl1, VE-cadherin (vascular endothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 58 publications
3
57
0
Order By: Relevance
“…It was shown that ADAM12L controls MMP14 activity through an αvβ3 integrin-dependent mechanism independent of its cytoplasmic tail or catalytic activity. 37 Similarly, ADAM12S may control the activity of E-cadherin sheddases like MMP14; however, our demonstration that ADAM12's catalytic activity is required for E-cadherin shedding, combined with findings showing that ADAM12 directly cleaves several membrane-bound substrates, including the type-II cadherin VE-cadherin, 38 supports a role for direct proteolysis of E-cadherin by ADAM12.…”
Section: Discussionmentioning
confidence: 66%
“…It was shown that ADAM12L controls MMP14 activity through an αvβ3 integrin-dependent mechanism independent of its cytoplasmic tail or catalytic activity. 37 Similarly, ADAM12S may control the activity of E-cadherin sheddases like MMP14; however, our demonstration that ADAM12's catalytic activity is required for E-cadherin shedding, combined with findings showing that ADAM12 directly cleaves several membrane-bound substrates, including the type-II cadherin VE-cadherin, 38 supports a role for direct proteolysis of E-cadherin by ADAM12.…”
Section: Discussionmentioning
confidence: 66%
“…For example, gene-targeting strategies in mice indicate ADAM12 as a key regulator in myogenesis 12 and adipogenesis, 13 while in vitro studies have assigned roles for ADAM12 in promoting cell fusion in osteoclasts 14 and trophoblasts. 15 ADAM12 also positively associates, and in some cases promotes, the progression of chronic disease states including multiple subtypes of cancer, [16][17][18] fibrosis, 19 and cardiac hypertrophy. 20 The secreted variant, ADAM12S, strongly links with cancer progression where serum levels are elevated in patients with highly-invasive metastatic breast cancer, while ADAM12S over-expression promotes breast cancer cell invasion.…”
Section: Diverse Proteases Coordinate Invasive Trophoblast Biologymentioning
confidence: 95%
“…10 Moreover, ADAM12 has recently been shown to cleave several cell adhesion molecules and components of the Notch signalling pathway, including vascular endothelial cadherin, vascular cell adhesion molecule 1, E-cadherin and delta-like ligand-1 (DLL1) 15,16,24 (Fig. 1).…”
Section: Diverse Proteases Coordinate Invasive Trophoblast Biologymentioning
confidence: 99%
“…Recent studies by Frohlich et al (12) showed that ADAM12 is expressed on ECs and can mediate ectodomain shedding/ cleavage of a number of EC membrane proteins, including Tie2, vascular endothelial (VE)-cadherin, and VEGFR2, with Tie2 shedding as the most robust of the proteins assessed. Moreover, there is evidence that Tie2 plays a critical role in perfusion recovery following experimental PAD (27), and cleavage of Tie2 leads to Tie2 activation and p-AKT (10,23).…”
Section: Adam12 Upregulation In Ischemia Occurs In Cd31-expressing Cementioning
confidence: 98%